120 likes | 242 Views
Section 3.5. Distributive Property. You must use the Distributive Property first. Then use the rules from Section 3.4 to solve. 3.5 Using the Distributive Property. Key Skills. Solve the equation:. 3( x – 4) = 48. 4( x + 1) = 16. 3 x – 12 = 48. 4 x + 4 = 16.
E N D
Distributive Property You must use the Distributive Property first. Then use the rules from Section 3.4 to solve.
3.5 Using the Distributive Property Key Skills Solve the equation: 3(x – 4) = 48 4(x + 1) = 16 3x – 12 = 48 4x + 4 = 16 3x – 12+ 12 = 48 + 12 4x + 4– 4 = 16 – 4 3x = 60 4x = 12 3 3 4 4 x = 20 x = 3
3.5 Using the Distributive Property Key Skills Solve the equation: 3y – 8 – y = 6 2(x + 5) = –16 2y – 8 = 6 2x + 10 = –16 2y – 8+ 8 = 6 + 8 2x + 10– 10 = –16 – 10 2y = 14 2x = –26 2 2 2 2 y = 7 x = –13
3.5 Using the Distributive Property Solve the equation: 4x – 8(x + 1) = 8 4t + 7 – t = 19 4x – 8x – 8 = 8 3t + 7 = 19 –4x – 8 = 8 3t + 7– 7 = 19 – 7 –4x – 8 + 8 = 8 + 8 3t = 12 –4x = 16 3 3 –4 –4 t = 4 x = –4
3.5 Using the Distributive Property Solve the equation, is the answer a solution? 2(x + 4) – 5 = 2x + 3 If all variables cancel, you must look at what’s left. 2x + 8 – 5 = 2x + 3 2x + 3 = 2x + 3 If what’s left is true, answer is all real numbers. 2x + 3 – 2x = 2x + 3 – 2x 3 = 3 If what’s left is not true, answer is no solution. Does this make sense?
3.5 Using the Distributive Property Solve the equation, is the answer a solution? 8x – 2(3x – 4) = 5x – 7. 8x + (–6x) + (8) = 5x – 7 2x + 8 = 5x – 7 2x + 8 – 2x = 5x – 7 – 2x 15 = 3x 8 = 3x – 7 3 3 5= x 7 + 8 = 3x – 7 + 7
-10 -10 3.5 Using the Distributive Property 4x – 3(2x + 4) = 8x – 25 4x – 6x – 12 = 8x– 25 –2x – 12 = 8x – 25 –2x = 8x – 25 + 12 –2x = 8x – 13 –2x – 8x = 8x – 13 – 8x –10x = –13 x = 1.3
-8 -8 3.5 Using the Distributive Property 4x – 7(x + 6) = 5x – 2 4x – 7x – 42 = 5x– 2 –3x – 42 = 5x – 2 –3x = 5x – 2 + 42 –3x = 5x + 40 –3x – 5x = 5x – 5x + 40 –8x = 40 x = –5
8 8 3.5 Using the Distributive Property 5x – 2(3x + 7) = 7x + 12 5x – 6x – 14 = 7x + 12 –x – 14 = 7x + 12 –x – 14 – 12 = 7x + 12 – 12 –x – 26 = 7x –x + x – 26 = 7x + x –26 = 8x –3.25 = x
Assignment Section 3.5 Page 145 # 12 – 45 (every 3rd)